d) 4/9 : 5/6 =
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\dfrac{13}{6}\)b) \(\dfrac{7}{18}\)c) \(5\) d) \(\dfrac{2}{3}\)
1.
a)x\(=\)\(\dfrac{7}{6}\)\(-\dfrac{2}{3}\)
x\(=\dfrac{1}{2}\)
b)x\(=\dfrac{9}{2}:\dfrac{3}{4}\)
x\(=6\)
a: \(=\dfrac{-8}{9}-\dfrac{6}{5}+\dfrac{8}{9}=-\dfrac{6}{5}\)
c: \(=\dfrac{2}{3}-\dfrac{1}{3}=\dfrac{1}{3}\)
a: \(\dfrac{5}{6}-\dfrac{4}{6}=\dfrac{5-4}{6}=\dfrac{1}{6}\)
b: \(\dfrac{7}{12}-\dfrac{6}{12}=\dfrac{7-6}{12}=\dfrac{1}{12}\)
c: \(\dfrac{7}{9}-\dfrac{2}{9}=\dfrac{7-2}{9}=\dfrac{5}{9}\)
d: \(\dfrac{16}{5}-\dfrac{9}{5}=\dfrac{16-9}{5}=\dfrac{7}{5}\)
Ta có:
Tập hợp A:
\(A=\left\{1;3;5;7;9\right\}\)
Tập hợp B:
\(B=\left\{0;1;2;4;5;6;8\right\}\)
Mà: \(C=A\cup B\)
\(\Rightarrow C=\left\{0;1;2;3;4;5;6;7;8;9\right\}\)
⇒ Chọn D
a) Ta có: \(\dfrac{-5}{7}\left(\dfrac{14}{5}-\dfrac{7}{10}\right):\left|-\dfrac{2}{3}\right|-\dfrac{3}{4}\left(\dfrac{8}{9}+\dfrac{16}{3}\right)+\dfrac{10}{3}\left(\dfrac{1}{3}+\dfrac{1}{5}\right)\)
\(=\dfrac{-5}{7}\cdot\dfrac{3}{2}\cdot\dfrac{21}{10}-\dfrac{3}{4}\cdot\dfrac{56}{3}+\dfrac{10}{3}\cdot\dfrac{8}{15}\)
\(=\dfrac{-9}{4}-14+\dfrac{16}{9}\)
\(=\dfrac{-1621}{126}\)
b) Ta có: \(\dfrac{17}{-26}\cdot\left(\dfrac{1}{6}-\dfrac{5}{3}\right):\dfrac{17}{13}-\dfrac{20}{3}\left(\dfrac{2}{5}-\dfrac{1}{4}\right)+\dfrac{2}{3}\left(\dfrac{6}{5}-\dfrac{9}{2}\right)\)
\(=\dfrac{-17}{26}\cdot\dfrac{13}{17}\cdot\dfrac{-3}{2}-\dfrac{20}{3}\cdot\dfrac{3}{20}+\dfrac{2}{3}\cdot\dfrac{-33}{10}\)
\(=\dfrac{3}{4}-1-\dfrac{11}{5}\)
\(=-\dfrac{49}{20}\)
câu a :
\(\dfrac{-8}{24}+\dfrac{-4}{12}=\dfrac{-1}{3}+\dfrac{-1}{3}=\dfrac{-2}{3}\)
câu b :
\(\dfrac{-20}{35}+\dfrac{16}{24}=\dfrac{-4}{7}+\dfrac{2}{3}=\dfrac{2}{21}\)
câu c :
\(\dfrac{-3}{9}+\dfrac{-6}{15}=\dfrac{-1}{3}+\dfrac{-2}{5}=\dfrac{-11}{15}\)
câu d :
\(\dfrac{3}{13}-\dfrac{4}{10}=\dfrac{3}{13}-\dfrac{2}{5}=\dfrac{-11}{65}\)
câu e :
\(\dfrac{5}{17}-\dfrac{9}{15}=\dfrac{5}{17}-\dfrac{3}{5}=\dfrac{-26}{85}\)
câu g :
\(\dfrac{9}{18}-\dfrac{6}{15}+\dfrac{3}{-9}=\dfrac{9}{18}-\dfrac{6}{15}+\dfrac{-3}{9}\\ =\dfrac{1}{2}-\dfrac{2}{5}+\dfrac{-1}{3}=\dfrac{-7}{30}\)
câu h :
\(\dfrac{5}{4}-\dfrac{1}{2}+\dfrac{-7}{8}=\dfrac{10}{8}-\dfrac{4}{8}+\dfrac{-7}{8}=\dfrac{-1}{8}\)
\(a.\frac{7}{5}+\frac{4}{7}-\frac{9}{10}=\frac{98}{70}+\frac{40}{70}-\frac{63}{70}=\frac{98+40-63}{70}=\frac{75}{70}\)\(=\frac{15}{14}\)
\(b.2+\frac{3}{4}x\frac{8}{5}=2+\frac{6}{5}=\frac{16}{5}\)
\(c.\frac{9}{8}-\frac{6}{5}:\frac{8}{5}=\frac{9}{8}-\frac{6}{5}x\frac{5}{8}=\frac{9}{8}-\frac{6}{8}=\frac{3}{8}\)
\(\frac{4}{9}:\frac{5}{6}=\frac{4}{9}\times\frac{6}{5}\)
\(=\frac{4\times6}{9\times5}\)
\(=\frac{8}{15}\)
@Bảo
#Cafe
TL
\(\frac{8}{15}\)
HT